2020
DOI: 10.1007/s00572-020-00941-3
|View full text |Cite
|
Sign up to set email alerts
|

Heritable genetic variation but no local adaptation in a pine-ectomycorrhizal interaction

Abstract: Local adaptation of plants to mycorrhizal fungi helps determine the outcome of mycorrhizal interactions. However, there is comparatively little work exploring the potential for evolution in interactions with ectomycorrhizal fungi, and fewer studies have explored the heritability of mycorrhizal responsiveness, which is required for local adaptation to occur. We set up a reciprocal inoculation experiment using seedlings and soil from four populations of Scots pine (Pinus sylvestris) from Scotland, measuring seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…This generalism is likely to be more pronounced in long-lived species, such as trees, where shifting environmental conditions may change the composition of EM communities, disrupting any adaptation that has taken place. In agreement with this, a previous study in this system found no evidence of local adaptation of Scots pine seedlings to EM fungi (Downie et al, 2020), and overall evidence for local adaptation in EM interactions is lacking (Rúa et al, 2018). Instead, host genotype effects on EM community composition found in other studies (Korkama et al, 2006;Patterson et al, 2018) may reflect differing nutritional requirements due to variation in growth rate, with hosts promoting associations that best meet their needs through preferential allocation (Bever, 2015), rather than reflecting evolution for increased or decreased association with specific fungal species.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This generalism is likely to be more pronounced in long-lived species, such as trees, where shifting environmental conditions may change the composition of EM communities, disrupting any adaptation that has taken place. In agreement with this, a previous study in this system found no evidence of local adaptation of Scots pine seedlings to EM fungi (Downie et al, 2020), and overall evidence for local adaptation in EM interactions is lacking (Rúa et al, 2018). Instead, host genotype effects on EM community composition found in other studies (Korkama et al, 2006;Patterson et al, 2018) may reflect differing nutritional requirements due to variation in growth rate, with hosts promoting associations that best meet their needs through preferential allocation (Bever, 2015), rather than reflecting evolution for increased or decreased association with specific fungal species.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of genetic signature in EM associations found here also highlights the potential importance of the life history of trees in shaping the evolutionary response to EM fungi (Batstone et al, 2018;Downie et al, 2020). High density-dependent mortality due to competition among seedlings for light and space may mean that selectivity, through association only with "high quality" EM partners, may impose significant competitive penalties via opportunity costs.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Soil fungi appear to play an important role in belowground adaptation in interior Douglas fir (Pickles et al 2015), and in coastal Douglas fir in British Columbia, population transfers across environmental gradients showed that height growth of trees declined as the difference between the ectomycorrhizal communities of the non‐native populations and those of the native hosts grew larger (Kranabetter et al 2015). Contrastingly, Downie et al (2020) found no indications of local adaptation to belowground fungal communities in a common‐garden trial with Scottish populations of Scots pine.…”
Section: Discussionmentioning
confidence: 91%